Experiential Communication as a Meaning Process in Shaping Agricultural Career Interest among Generation Z : A Cross-Educational Perspective - Nurmelati Septiana; Luthfi Fatah (Fakultas Ilmu Sosial UIN Sumatera Utara Medan, 2026)
This study analyzes experiential communication as a meaning-making process in influencing agricultural career interest in Generation Z through a cross-level education approach. The study used a mixed-methods explanatory sequential design, with quantitative data from 136 students of SMK Pertanian Banjarbaru and qualitative data through a directed group discussion (FGD) with ULM agribusiness students. The results showed that career interests were in the very high category, with the dominance of affective and conative dimensions over cognitive, indicating that interests were more shaped by experience and emotional involvement than conceptual understanding. The level of student motivation is also very high, characterized by a combination of intrinsic and extrinsic motivation that reflects the ongoing internalization process. Qualitative findings confirm that experiential communication functions as a transformational communication mechanism that is able to reduce negative stereotypes and form a new understanding of the potential of the agricultural sector. Thus, this study emphasizes that experiential communication is a process of forming meaning that plays an important role in shaping the career orientation of Generation Z in the agricultural sector.